The effect of food prescription programs on chronic disease management in primarily low-income populations: A systematic review and meta-analysis. Issue 3 (September 2022) - Haslam, Alyson; Gill, Jennifer; Taniguchi, Tori; Love, Charlotte; Jernigan, Valarie Bluebird
Background: Having low-income limits one's ability to purchase foods that are high in nutritional value (e.g. vegetables and fruits (V/F)). Higher V/F intake is associated with less diet-related chronic disease. Food pharmacy programs are potential solutions to providing V/F to low-income populations with or at-risk for chronic disease.Aim: This systematic review aimed to determine the effect of food pharmacy programs, including interventions targeting populations at-risk for chronic disease.Methods: We searched Pubmed and Google Scholar databases for studies reporting on food pharmacy interventions and outcomes (hemoglobin A1c, body mass index (BMI), V/F intake, and blood pressure). We calculated pooled mean differences using a random-effects model. Seventeen studies met our inclusion criteria; 13 studies used a pre/post study design, three used a randomized controlled trial, and one was a post-survey only.Results: We found that the pooled mean daily servings of V/F (0.77; 95% CI: 0.30 to 1.24) was higher and BMI (−0.40; 95% CI: −0.50 to −0.31) was lower with food pharmacy interventions We did not find any differences in the pooled mean differences for hemoglobin A1c or systolic blood pressure.Conclusion: Findings posit that food pharmacy programs delivered to primarily low-income individuals with comorbidities may be a promising solution to improving V/F intake and possibly overall diet in these populations.